Allosterically gated enzyme dynamics in the cysteine synthase complex regulate cysteine biosynthesis in Arabidopsis thaliana - Feldman-Salit, Anna; Wirtz, Markus; Throm, Christian; Hell, Rüdiger; Wade, Rebecca C. (Structure, 2012)
Summary: Plants and bacteria assimilate sulfur into cysteine. Cysteine biosynthesis involves a bienzyme complex, the cysteine synthase complex (CSC), which consists of serine-acetyl-transferase (SAT) and O-acetyl-serine-(thiol)-lyase (OAS-TL) enzymes. The activity of OAS-TL is reduced by formation of the CSC. Although this reduction is an inherent part of the self-regulation cycle of cysteine biosynthesis, there has until now been no explanation as to how OAS-TL loses activity in plants. Complexation of SAT and OAS-TL involves binding of the C-terminal tail of SAT in one of the active sites of the homodimeric OAS-TL. We here explore the flexibility of the unoccupied active site in Arabidopsis thaliana cytosolic and mitochondrial OAS-TLs. Our results reveal two gates in the OAS-TL active site that define its accessibility. The observed dynamics of the gates show allosteric closure of the unoccupied active site of OAS-TL in the CSC, which can hinder substrate binding, abolishing its turnover to cysteine.